2014
DOI: 10.1063/1.4904852
|View full text |Cite
|
Sign up to set email alerts
|

First stage of CoSi2 formation during a solid-state reaction

Abstract: The kinetics of CoSi2 formation via a solid-state reaction between CoSi and single crystal Si has been the object of many studies in the past. Because of the importance of nucleation, complex kinetics has been reported. In this work, we investigate CoSi2 formation kinetics with in-situ diffraction during isothermal annealing of CoSi films on Si (100). In-situ measurements allow capturing the initial stage of CoSi2 formation. An initial t3/2 time-dependent evolution is observed and attributed to 3D growth of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…These models are based on different approximations and different phenomena. However, all of the models consider the diffusion along the interfaces and they conclude that the product phase should reach a stationary thickness that depends on the kinetics parameters, in accordance with the experimental results [14][15][16][17]19]. The models also led to a relatively similar particle shape.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…These models are based on different approximations and different phenomena. However, all of the models consider the diffusion along the interfaces and they conclude that the product phase should reach a stationary thickness that depends on the kinetics parameters, in accordance with the experimental results [14][15][16][17]19]. The models also led to a relatively similar particle shape.…”
Section: Introductionsupporting
confidence: 77%
“…Several experimental studies [14][15][16][17][18][19] reported the presence of a discontinuous phase as the first results of the reaction between the two other phases. However, the entire particle shape has not been reported; thus, it is not possible to compare these experimental results with existing models [13,20,22,23].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Using transmission electron microscopy (TEM) and in situ X-ray diffraction (XRD) experiments with high-intensity synchrotron radiation, Lucadamo et al [56] evidenced a two-stage reaction mechanism in Nb/Al multilayer thinfilms. Delattre et al found CoSi2 precipitates at the CoSi/Si interface by TEM [58] . Precipitates of Al9Co2 that quickly grow to form a dense layer were observed by atom probe tomography (APT) as the first product of the Al/Co reaction [59].…”
Section: Mechanisms Of Formationmentioning
confidence: 99%